Neuroimaging the Serial Position Curve: A Test of Single-Store Versus Dual-Store Models. - Talmi, Deborah; Grady, Cheryl L.; Goshen-Gottstein, Yonatan (Psychological Science., 2005)
A study was conducted to examine the distinction between retrieval from short-term memory-working memory (STM-WM) and long-term memory (LTM) in healthy adults. Data were gathered from experiments in which ten right-handed adults aged 20–24 years were scanned using functional magnetic resonance imaging while they recognized items from early or late serial positions. Findings revealed that the recognition of early items uniquely activated areas of the brain that are traditionally associated with LTM and that none of these areas were activated for retrieval of late items. The implications of these findings are discussed.